Expression 68414

The expression 3x - [2 - (2x - 1) + x] is given. Determine for which numbers x the expression is equal to 0.

Correct answer:

x =  0.75

Step-by-step explanation:

3x[2(2x1)+x]=0  3 x(2(2 x1)+x)=0  4x=3  x=43=0.75



Did you find an error or inaccuracy? Feel free to write us. Thank you!










Tips to related online calculators
Do you have a linear equation or system of equations and looking for its solution? Or do you have a quadratic equation?

You need to know the following knowledge to solve this word math problem:

Related math problems and questions: